Impact of Highly Active Antiretroviral Therapy (HAAT) on Lipid Profiles of HIV Patients - Murshed, Khaled Mahbub; Shahdaty, Syeda Kimia; Azad, Md Abul Kalam; Ahmed, Nazma (Community Based Medical Journal, 2025)
Highly active antiretroviral therapy (HAART) has resulted in a significant reduction in morbidity and death in HIV patients. However, it has also resulted in the appearance of significant short- and long-term negative effects. The complication of HAART that is currently generating the most interest and concern is an elevated cardiovascular risk.The aim of this study was to assess the impact of highly active antiretroviral therapy on fasting blood lipid profiles in HIV patients. This prospective, observational study was conducted in the ART Centre of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, between January 2020 and June 2021. A total of 49 HIV sero-positive patients (diagnosis based on rapid diagnostic test) attending ART Centre of Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital were included in this study. We found that 9.7% had TC ≥200. The majority 80.6% patients belonged to HDL-C <40 (mg/dl) and the mean was 31.4±9.26 (gm/dl). Regarding LDL, 9.7% of patients had LDL-C (>130 mg/dl), and the mean was 85.34±28.79 (gm/dl). About half 51.6% of patients belonged to TG >150 (mg/dl) and the mean was 154.46±59.62 (gm/dl). We found that 87.1% of patients developed dyslipidaemia before treatment and 83.9% after HAART. TG levels were significantly elevated after HAART, but TC, HDL-C, and LDL-C levels almost remained the same between baseline and after HAART. Development of dyslipidaemia was found in more than two-thirds (83.9%) of the patients after HAART. HIV-infected patients receiving WHO recommended first-line of HAART have a high prevalence of lipid profile derangement. CBMJ 2025 July: vol. 14 no. 02 P:40-47